The influence of renal function on surgical outcomes of vitrectomy in patients with proliferative diabetic retinopathy - Yuan, Qiongzhen; Yang, Zhouquan; Fan, Wei; Chen, Xiaofan; Zou, Huan; Yuan, Rongdi (Frontiers in Endocrinology, 2025)
PurposeTo investigate the influence of renal function on the surgical outcomes of vitrectomy in patients with proliferative diabetic retinopathy (PDR).MethodsA secondary analysis was conducted on data from a retrospective cohort study.ResultsA total of 128 eyes with PDR that underwent pars plana vitrectomy (PPV) and were followed up for at least 2 years were enrolled, including 65 eyes in the impaired renal function (IRF) group and 63 eyes in the normal renal function (NRF) group. No significant between-group differences were observed in the proportion of cataract surgery (p = 0.722), intraoperative retinal photocoagulation (p = 0.476), gas tamponade (p = 0.932), silicone oil tamponade (p = 0.254), retinal dialysis and/or iatrogenic retinal breaks (p = 0.447), and 23- or 25-gauge (G) microincision vitrectomy surgery (MIVS) (p = 0.160). Similarly, intergroup comparisons showed no significant differences in the proportion of reoperation (p = 0.883), postoperative vitreous hemorrhage (VH) and/or retinal detachment (RD) (p = 0.919), postoperative neovascular glaucoma (NVG) (p = 0.600), and postoperative diabetic macular edema (DME) (p = 0.794). Notably, the IRF group had worse baseline best corrected visual acuity (BCVA) (p = 0.039) and showed greater BCVA improvement at 3 months (p = 0.008), 6 months (p = 0.047), 1 year (p = 0.007), 2 years (p = 0.003), 3 years (p = 0.009), and 4 years (p = 0.024) after surgery. However, there was no significant difference in postoperative BCVA between the two groups at each follow-up time (all p > 0.05).ConclusionsRenal insufficiency does not adversely affect the surgical outcomes of PPV in patients with PDR.